Malaria and advising the traveller. (December 2021) - Mabayoje, Diana Ayoola; Longley, Nicky
Abstract: Malaria is a preventable, mosquito-borne parasitic infection that remains one of the leading causes of imported fever, hospitalization and death in travellers returning from Sub-Saharan Africa. Early symptoms of malaria infection can mimic other common conditions presenting to healthcare settings. A high index of suspicion and early diagnosis and management, alongside patient education and prevention methods, can greatly reduce morbidity and mortality from malaria worldwide. In this article we aim to cover the different types of malaria, individuals at particular risk of malaria acquisition, malaria prevention, treatment and key advances. We will focus on falciparum malaria as this causes the greatest morbidity and mortality.